Caracterização histológica e histoquímica do gânglio nervoso de Loxosceles (Aracnida: Araneae) - Carvalho, Edimara Salete de (2022)
Spiders of the genus Loxosceles, in public health, represent a risk to the population in general, as they are responsible for thousands of accidents per year in Brazil, where the concentration of cases involving this genus is in Paraná. Because they have a small size, color similar to the environment they live in or dark color and have nocturnal habits, it is not immediately observed the presence of these spiders, as well as complicates its study. Their bite is not often immediately noticed, it has a necrotizing action and in severe cases it can cause anemia and acute renal failure, leading to the patient's death. Due its importance, a morphological and histochemical study of these organisms to deepen the methods of prophylaxis and accident prevention for the population.The objective of this paper is to test two inclusion and coloring methods to observe which inclusion method is the best in the preservation of the material and which staining method will satisfactorily evidence the nerve ganglion tissue of spiders of the genus Loxosceles. To carry out this work, 20 specimens were collected in the city of Dois Vizinhos-PR, taken to the UTFPR-Dois Vizinhos and anesthetized to have their cephalothorax perforated (for better penetration of the reagents) and then euthanized. They were fixed in Carnoy for three days, and separated into groups: 1-Inclusion in Paraffin with beeswax and staining with Hematoxylin and Eosin, 2-Inclusion in Paraffin with beeswax and PAS histochemistry, 3-Inclusion in Historesin and staining of Hematoxylin and Eosin and 4-Inclusion in Historesin and PAS histochemistry. After the slides were fully assembled, the photographic record was made and the preservation of the slides was analyzed under a light microscope and during the analysis, the sections of the different groups were compared to each other to determine which of the groups presented the best morphation of the organization. faith fixative successfully completed, if the embedding with paraffin or Historesin was correct and which faith coloring best to highlight the target structure. It is concluded, with this work, that the inclusion in paraffin and the PAS staining were more effective for highlighting the nervous ganglion, preserving and better showing the target structure.